2021
DOI: 10.1063/5.0035045
|View full text |Cite
|
Sign up to set email alerts
|

Time resolved detection of the S(1D) product of the UV induced dissociation of CS2

Abstract: The products formed following the photodissociation of UV (200 nm) excited CS 2 are monitored in a time resolved photoelectron spectroscopy experiment using femtosecond XUV (21.5 eV) photons. By spectrally resolving the electrons we identify separate photoelectron bands related to the CS 2 + hν −→ S( 1 D) + CS and, CS 2 + hν −→ S( 3 P) + CS dissociation channels which show different appearance and rise times. The measurements show that there is no delay in the appearance of the S( 1 D) product contrary to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
3
8
0
Order By: Relevance
“…This compares with the unweighted trajectories which give a branching ratio of 1 : 1.9 with a remainder bound contribution of 24% at t = 1 ps. Both the biased and the unbiased branching ratios are in reasonable agreement with recent time resolved photoelectron spectroscopy measurements, 4,36 and those measured in nanosecond experiments measuring the final products 37–43 which provide values around 1 : 2.5 and 1 : 3 respectively. The 1 : 3 ratio from the nanosecond experiments is based on an average of a number of measurements which have provided varied estimates between 4 : 1 and 1 : 6.…”
Section: Resultssupporting
confidence: 88%
“…This compares with the unweighted trajectories which give a branching ratio of 1 : 1.9 with a remainder bound contribution of 24% at t = 1 ps. Both the biased and the unbiased branching ratios are in reasonable agreement with recent time resolved photoelectron spectroscopy measurements, 4,36 and those measured in nanosecond experiments measuring the final products 37–43 which provide values around 1 : 2.5 and 1 : 3 respectively. The 1 : 3 ratio from the nanosecond experiments is based on an average of a number of measurements which have provided varied estimates between 4 : 1 and 1 : 6.…”
Section: Resultssupporting
confidence: 88%
“…Previously, TRPEI study by Horio et al suggested that S­( 1 D 2 ) reaction products appear after a certain latency time, which suggests the presence of an intermediate state for the singlet dissociation channel. In this sense, our conclusion is consistent with that of Horio et al Minns and colleagues proposed a slightly different kinetic model, which assumes that the singlet reaction products are generated directly from 1 B 2 ; however, we found that the experimental data presented here cannot be well-explained with their model. , They measured similar time profiles with the cross-correlation time of 180 fs and performed the analysis without considering molecular signals. As presented in section S6 of the Supporting Information, when the experimental data shown in Figure c are convoluted with a Gaussian function with a full width at half-maximum (fwhm) of 180 fs, the time profiles become much smoother and the position of initial signal rise become elusive.…”
supporting
confidence: 91%
“…As presented in section S6 of the Supporting Information, when the experimental data shown in Figure c are convoluted with a Gaussian function with a full width at half-maximum (fwhm) of 180 fs, the time profiles become much smoother and the position of initial signal rise become elusive. Thus, we believe the difference between the two studies largely originates from the low temporal resolution and the lack of consideration of molecular signals. , …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental techniques used to study this CS 2 reaction cover a wide range. Photoelectron spectroscopies 11,12,14,[18][19][20][21] are generally sensitive to the instantaneous electronic state of the system. Ion momentum imaging with state-selective resonanceenhanced multi-photon ionization (REMPI) has yielded information on the dissociation velocity distribution of the various breakup channels 22,23 .…”
Section: Introductionmentioning
confidence: 99%